Critical Determinants of Rice Tungro Disease Devastation and its Vector Population Dynamics in Bangladesh (Bangladesh Rice Journal, 2026)
Rice Tungro disease caused by Rice Tungro Viruses (RTBV and RTSV) transmitted by vector Green Leaf Hopper (GLH), Nephotettix virescens.  Every year tungro disease infection is devastating in several rice growing areas in Cumilla region as well as country-wide. Rice Tungro disease is a major limiting factor of rice production. In Bangladesh, yield loss due to tungro was reported to be as high as 100% under severe conditions. Three crop rice (Rice-Rice-Rice) areas are most vulnerable to Tungro disease infection. Weather parameters like temperature, rainfall, relative humidity and light trap data of GLH from BRRI Cumilla and GLH data from rice field of Nangalkot Upazila were investigated. The previous tungro disease data were collected from the survey of different Upazila of Cumilla district during 2017 to 2024. In the farmers field condition, GLH data were collected by hand sweeping and light trap from both seedbed to main fields. From the study, intensive rice cultivation (Rice- Rice- Rice), susceptible rice varieties, presence of abundant GLH in the seedbed (20 times more) as well as viruses with disease symptom, monthly average maximum (>25 oC)) and minimum temperature (